(untitled) (Ameghiniana, 2013)
ARENIGIAN GRAPTOLITES FROM THE RIO CAJAS SECTION (ACOITE FORMATION), JUJUY PROVINCE, ARGENTINA. A graptolite association from Quebrada del Río Cajas is described. The occurrence of Didymograptus (Corymbograptus) balticus together with Acrograptus filiformis in lower levels of the Acoite Formation indicates an Early Arenig age for these horizons. This association is described for the first time in Argentina and corresponds to the D. (Corymbograptus) balticus Biozone from Sweden, equivalent to the lower part of the D. (Coryrnbograptus) deflexus Subzone of the British zonation.